Bilayer Membrane Composed of Mineralized Collagen and Chitosan Cast Film Coated With Berberine-Loaded PCL/PVP Electrospun Nanofiber Promotes Bone Regeneration - Zhang, Yuhan; Wang, Ting; Li, Juan; Cui, Xiaoming; Jiang, Mingxia; Zhang, Mogen; Wang, Xiaoli; Zhang, Weifen; Liu, Zhijun (Frontiers in Bioengineering and Biotechnology, 2021)
Bone defects are difficult to repair and reconstruct as bone regeneration remains technically challenging, with exogenous factors required to accelerate this process. Biodegradable synthetic scaffolds are promising materials for stimulating bone tissue repair. In this study, we investigated whether a bilayer membrane that includes mineralized collagen (MC) and chitosan (CS) delivering berberine (BER)—a typical Chinese herbal monomer—could promote bone healing in a rat model. An MC/CS cast film was coated with polycaprolactone (PCL)/polyvinylpyrrolidone (PVP) electrospun nanofibers loaded with BER, yielding the BER@PCL/PVP-MC/CS bilayer membrane. The 3-dimensional structure had nanofibers of uniform diameter and showed good hydrophilicity; the bilayer membrane showed favorable mechanical properties. BER@PCL/PVP-MC/CS enhanced the proliferation and attachment of MC3T3-E1 cells in vitro and induced bone regeneration when implanted into a rat femoral bone defect. These findings provide evidence that BER@PCL/PVP-MC/CS has clinical potential for effective bone repair.